Viewshed and sense of place as conservation features: A case study and research agenda for South Africa's national parks - Jaco Barendse; Dirk Roux; Waldo Erfmann; Johan Baard; Tineke Kraaij; Cara Nieuwoudt (Koedoe: African Protected Area Conservation and Science, 2016)
Sense of place (SoP) refers to the meanings and values that people attach to places. The concept can be used to frame how people engage or form a connection with the natural environment. At a sensory level, SoP is influenced by people’s visual experiences, which in turn can be linked to the concept of viewsheds. Viewsheds can be transformed, either abruptly (e.g. by infrastructure development such as wind turbines) or more gradually (e.g. by non-native trees invading a landscape). In this study, we focus on the Garden Route National Park to explore the potential importance of viewsheds as a conservation feature, specifically in the context of non-native (especially invasive) tree species. Using mixed information sources, we explore the potential role of invasive trees on experiences of visitors to this protected area and speculate on how viewsheds may shape SoP associations and how such associations may inform protected area management. Our investigation shows that people’s experiences regarding natural and modified viewsheds are varied and intricate. Both SoP and viewsheds have the potential to inform conservation action, and these concepts should form an integral part of objective hierarchies and management plans for national parks. However, while legislation and park management plans make provision for the use of these concepts, associated research in South Africa is virtually non-existent. We conclude by proposing a conceptual model and research agenda to promote the use of viewsheds and SoP in the management of national parks in South Africa.